Improving Public and Environmental Health Through Rheumatoid Screening and Education on Environment Pathogenic Fungal Contamination - Maat, Suprapto; Prayekti, Endah; Nugraha, Gilang; Ramadani, Vania Nur; Melindah, Winda; Mukarramah, Imraatul (Indonesia Berdaya, 2026)
People working in agricultural environments with high humidity levels are at greater risk of exposure to pathogenic fungi, which can trigger infections of the skin, nails, and respiratory tract, especially in individuals with weakened immune systems. On the other hand, the elderly are vulnerable to health decline, including autoimmune diseases such as rheumatoid arthritis (RA), which can cause joint inflammation, tissue damage, and progressive disability. This community service activity aims to increase public knowledge about the dangers of pathogenic fungal contamination and to conduct early detection of RA through Rheumatoid Factor (RF) testing. Education was delivered interactively using lectures, discussions, and visual media, accompanied by pre- and post-tests, as well as RF testing using the latex agglutination method. This community service activity was attended by 33 participants. Results showed an increase in knowledge from 58% to 91% after the education, with all 33 RF test participants receiving non-reactive results. This program demonstrates that the combination of education and simple testing can increase public preventive awareness and is suitable for adaptation in other areas with similar risk characteristics.